Tipologi Studi Hadis Kontemporer di Indonesia (Studi Terhadap Artikel Jurnal Terindeks Moraref tahun 2017-2021) - Ade Pahrudin (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Typology of Contemporary Hadith Studies in Indonesia (Study of Moraref Indexed Journal Articles 2017-2021)This article aimed to analyze hadith study articles on the e-journal of Moraref portal to map the typology of contemporary hadith studies in Indonesia. This research is a literature research in the form of descriptive-analytic. The analysis method is content-analysis with inductive-clustering approach. The main data in this study are e-articles on hadith studies contained in the Moraref portal of the Ministry of Religion from 2017-2021. The results of this study indicate a positive contribution to the development of Islamic studies, especially hadith after the digitization of Islamic knowledge in Indonesia, because it facilitates knowledge-sharing and knowledge-access. There are 672 e-articles divided into seven typologies centered on two points of view or perspectives on hadith; first, hadith as a scientific tool; This view produces three typologies of contemporary hadith studies in Indonesia, namely; Hadith science, Hadith figures and thoughts, Scientific integration with other branches of science. Second, Hadith as a teaching; This perspective gives rise to three categories or characteristics in hadith research in Indonesia; Hadith understanding method, Thematic hadith study, Living hadith. Both of these points of view were viewed in a typology of hadith development studies